RITUALITAS KEAGAMAAN DAN TOLERANSI BERAGAMA DALAM PERSPEKTIF TINDAKAN SOSIAL MAX WEBER - Muhammad Tharom (Journal Khafi : Journal Of Islamic Studies, 2025)
Religious tolerance has long been a subject of interest among social scientists, particularly through Max Weber’s concept of social action, which is relevant for understanding religious diversity in everyday life. This study aims to examine Max Weber’s theory of social action and relate it to the practice of religious tolerance in a business setting, specifically at the Razzaq refill drinking water depot. The study employs a qualitative method with a descriptive qualitative approach. The findings indicate that religious tolerance can be understood through four types of social action: traditional action, affective action, instrumental rationality, and value rationality. The application of these four types of social action is reflected in the interactions between consumers and employees, leading to increased understanding, positive feedback, and the creation of a sense of comfort and tranquility for employees in carrying out their religious rituals as part of their daily activities.